Restoring Edentulous Mandible with an Implant-Retained Overdenture in a Day by Means of Flapless Surgery and Stereolithographic Surgical Guide: a Case Report - Ilser Turkyilmaz (eJournal of Oral Maxillofacial Research, 2019)
Background: Digital revolution is here and becoming more and more influential in our daily lives by transforming several things such as our habits, interactions with other people and the practice of dentistry. In implant dentistry, the newer methods by using cone-beam computed tomography and computer-aided design and computer-aided manufacturing recently offer more predictable and aesthetics outcomes in a shorter period of treatment time when compared to the traditional prosthetic procedures.